THE EFFECT OF PROMOTION AND PRODUCT FEATURE ON CUSTOMER LOYALTY (STUDY AT ONE OF KNITTING COMPANIES IN BANDUNG CITY) - Haris Nurdiansyah (STMIK Mardira Indonesia, Bandung, 2021)
Researchers studied to determine the effect of promotions and product features on customer loyalty at a knitting company in the city of Bandung. Moreover, this research analyzes the factors that have the most dominant influence between promotions and product features on customer loyalty at a knitting company in the city of Bandung, which is the object of this study for as many as 100 customers using a questionnaire. Based on research using flow analysis, the promotion and product feature variables at a knitting company in Bandung are proven significant. The study results show that promotion has a significant effect on customer loyalty, and product features have a significant effect on customer loyalty. Furthermore, the study results indicate that promotions and product features can create loyal customers. Researchers suggest that companies can provide all the rights that can affect promotion variables and product features to provide customer awareness so that customer loyalty does not decrease; on the contrary, it has increased. Keywords: Promotion, Product Feature, Customer Loyalty